Optimizing Paint Distribution Routes with CVRP-Based Ant Colony Optimization - Dien Fairuz Dzakiyyah Bakri; Farida Pulansari (EPI International Journal of Engineering, 2025)
PT XYZ is a manufacturing company engaged in paint production with complex product distribution activities. The company currently determines distribution routes based on drivers’ experience and habits without systematic route optimization, resulting in less efficient travel distances and distribution costs. This study aims to optimize product distribution routes using the Ant Colony Optimization (ACO) method based on the Capacitated Vehicle Routing Problem (CVRP). The study utilizes data consisting of distributor locations, inter distributor distances, product demand, vehicle capacity, and the company’s actual distribution costs. The ACO method was applied to generate alternative distribution routes by considering vehicle capacity constraints and minimizing total travel distance. The results indicate that the proposed routes generated using ACO based on CVRP are more efficient than the company’s existing routes. The optimization reduced the total travel distance by 6.79% and lowered distribution costs by 6.40%. These findings demonstrate that the ACO method is effective in improving distribution efficiency and can serve as a decision-support approach for distribution route planning at PT XYZ.